Mental Health Literacy and Help-Seeking Behaviours Among Undergraduate Pharmacy Students in Abha, Saudi Arabia - Almanasef M (Dove Medical Press, 2021)
Mona Almanasef Department of Clinical Pharmacy, College of Pharmacy, King Khalid University, Abha, Saudi ArabiaCorrespondence: Mona AlmanasefCollege of Pharmacy, King Khalid University, P.O. Box 960, Abha, 61421, Saudi ArabiaEmail malmanasaef@kku.edu.saBackground: The serious mental health problems experienced by university students could have a negative impact on their long-term mental, social and physical health as well as their academic achievements. The ability to recognise a condition, and knowledge about mental health issues and sources of help, are among the factors influencing help-seeking behaviour in young individuals. This study was conducted to examine the mental health literacy among undergraduate pharmacy students and to assess whether mental health literacy is linked to a stronger intention to seek help.Methods: This prospective cross-sectional study used an online self-administered questionnaire. A total of 271 pharmacy students at King Khalid University completed the questionnaire and agreed to participate in the study.Results: The mental health literacy in the current study (M=112.53) was found to be lower than that reported in international research using the MHLS. Students with no history of mental health issues scored significantly higher in help-seeking behaviours from informal sources (M=23.65, SD=6.88) than those with a previous history (M=19.03, SD=7.58), F (1, 269)=11.76, p=0.001. The study revealed a significant positive correlation between mental health literacy and help-seeking behaviours r(271)=0.26, p< 0.01.Conclusion: This study demonstrates that there is a positive correlation between mental health literacy and help-seeking behaviours. Implementing appropriate interventions could be a key priority in improving the mental health literacy and help-seeking behaviour of students.Keywords: mental health literacy, help-seeking behaviours, pharmacy students, Saudi Arabia